Assessing the financial performance of hospitals in the Covid-19 crisis: a case study of a hospital in Tehran - Behnam Hassan-Nezhad; Seyed Masood Moosavi-Nezhad; Hamzeh Enayat (فصلنامه ابن سینا)
Background and aims: The Covid-19 was considered as a health shock and led to stochastic demand, which affected the financial performance of the hospitals in 2020.This study aimed to examine the financial performance of a non-training general and governmental hospital in Tehran city, in the first peak of Covid-19. Methods: It was a descriptive and cross-sectional study. Cost headings, revenue centers, and the amount of profit / loss of the selected  hospital were calculated for four months of the first peak of Covid-19 pandemic in Iran (20 March 2020 to 21 July 2020).The mentioned items and the number of patients referred in different wards of the hospital were compared with those of the equivalent months in previous year to determine the effect of Covid-19 on financial performance. Percentage changes in costs, revenues, number of patients, and the revenue-to-cost ratio were analyzed. Results: Costs and revenues were reported at about 75 and 128 billion rials, respectively. Our resuls showed that costs decreased by 3%, revenues increased by 21%, and finally, hospital profitability increased by 84%. The average of the revenue-to-cost ratio in the study period was estimated as 1.7. The hospiral bed occupancy rate reduced by 20%. Conclusion: Although the financial loss of the hospital was expected due to the decrease in demand for hospital services in the first peak of Covid-19 pandemic, the reduction in variable costs and the increase in annual service tariffs by the Ministry of Health and Medical Education largely prevented losses.